Identifikasi Kebutuhan dan Strategi Intervensi dengan Media Virtual Reality pada Anak dengan Cerebral Palsy Ringan - Ningsih, Kholifatul Novita; Kasirah, Irah; Mulyeni, Trisna; Aulia, Difa Syahidah Izzah; Nugroho, Mayang (Jurnal Pendidikan Kebutuhan Khusus, 2025)
This study aims to identify the specific needs of children with mild cerebral palsy (CP) and to explore the potential use of Virtual Reality (VR) technology as an educational and rehabilitative intervention medium within the context of special education. Employing an exploratory qualitative approach, the research was conducted at SLBN YPAC Jakarta through participatory observation, interviews with teachers, therapists, and parents, as well as document analysis. The findings indicate that children with mild CP require intensive support in both fine and gross motor coordination, yet they demonstrate adequate cognitive capacity and a positive response to visual and interactive learning. Teachers and parents showed strong acceptance toward the use of VR, although technical readiness, teacher training, and limited device availability remain key challenges. VR media has significant potential to enhance children’s motor and cognitive skills through activity simulations, real-time feedback, and multisensory stimulation that supports neuroplasticity processes. These findings highlight the importance of contextual needs assessment as the foundation for developing VR-based intervention models and media that are adaptive, applicable, and inclusive, enabling their practical implementation in special education settings in Indonesia.